2016
DOI: 10.1093/molbev/msw198
|View full text |Cite
|
Sign up to set email alerts
|

Loss and Gain of Human Acidic Mammalian Chitinase Activity by Nonsynonymous SNPs

Abstract: Acidic mammalian chitinase (AMCase) is implicated in asthma, allergic inflammation, and food processing. Little is known about genetic and evolutional regulation of chitinolytic activity of AMCase. Here, we relate human AMCase polymorphisms to the mouse AMCase, and show that the highly active variants encoded by nonsynonymous single-nucleotide polymorphisms (nsSNPs) are consistent with the mouse AMCase sequence. The chitinolytic activity of the recombinant human AMCase was significantly lower than that of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 37 publications
(67 reference statements)
4
58
0
Order By: Relevance
“…We observed no difference in AMCase protein levels in BAL fluid between controls and patients with ILD or asthma (Figure 7B and Figure S7B). AMCase activity can vary with common gene polymorphisms (Seibold et al, 2009; Aminuddin et al, 2012; Okawa et al, 2016), but no differences in exo-or endochitinase activity were observed in BAL fluid between controls and patients with ILD; however, notably, human endochitinase activity in all but one patient sample was comparatively lower than in mouse BAL fluid, and in contrast to normal β-N-acetylglucosaminidase activity (Figure 7C), supporting prior studies describing relatively inefficient enzymatic activity among common human AMCase isoforms (Seibold et al, 2009; Goedken et al, 2011; Okawa et al, 2016). Further, as assessed using CBD-reactive material, significantly increased amounts of chitin polymers were present in BAL fluid from patients with ILD as compared to healthy controls (Figure 7D).…”
Section: Resultsmentioning
confidence: 99%
“…We observed no difference in AMCase protein levels in BAL fluid between controls and patients with ILD or asthma (Figure 7B and Figure S7B). AMCase activity can vary with common gene polymorphisms (Seibold et al, 2009; Aminuddin et al, 2012; Okawa et al, 2016), but no differences in exo-or endochitinase activity were observed in BAL fluid between controls and patients with ILD; however, notably, human endochitinase activity in all but one patient sample was comparatively lower than in mouse BAL fluid, and in contrast to normal β-N-acetylglucosaminidase activity (Figure 7C), supporting prior studies describing relatively inefficient enzymatic activity among common human AMCase isoforms (Seibold et al, 2009; Goedken et al, 2011; Okawa et al, 2016). Further, as assessed using CBD-reactive material, significantly increased amounts of chitin polymers were present in BAL fluid from patients with ILD as compared to healthy controls (Figure 7D).…”
Section: Resultsmentioning
confidence: 99%
“…We expressed and purified Protein A‐AMCase‐V5‐His from the periplasmic fraction of Escherichia coli as described previously . The protein‐containing fractions were desalted using PD MidiTrap G‐25 (GE Healthcare, Milwaukee, WI, USA) equilibrated with TS buffer [20 m m Tris‐HCl (pH: 7.6), 150 m m NaCl and protein inhibitor (Complete Mini; Roche Diagnostics, Basel, Switzerland)].…”
Section: Methodsmentioning
confidence: 99%
“…Acidic mammalian chitinase has attracted considerable attention due to its altered expression under certain pathological conditions related to immune response, such as in an induced asthma and antigen‐induced allergic lung inflammation mouse models . Some polymorphisms and haplotypes in the AMCase gene are associated with bronchial asthma in humans and inhibition of its activity has been suggested as a therapeutic strategy against asthma . Furthermore, AMCase has been shown to be involved in eye and stomach diseases .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AMCase also functions as a critical initiator of protective type 2 responses to intestinal nematodes18. In addition, several genetic variants of AMCase are associated with bronchial asthma in humans19202122.…”
mentioning
confidence: 99%